Causality between Corporate Governance and Firm PerformanceEvidence from Borsa Istanbul (BIST) - (:unkn) unknown (My University, 2017)
0

Due to increasing pace of globalization and recent corporate scandals, corporate governance arrangements have attracted attention and become an area of discussion. Besides securing interests of shareholders, it is also proposed that corporate governance practices enhance shareholders’ value. Based on a data set from Borsa Istanbul (BIST) and associated BIST Corporate Governance Index for the period between 2007 and 2015, this study attempts to evaluate whether market and operating performances of firms are affected from the level of adopted corporate governance practices. The study also addresses the issue of causality through systems equations constructed with selected instrumental variables. The findings revealed that corporate governance rating positively influenced stock market performance which was measured by Tobin’s Q, and operating performance which was measured by return on assets. The study also found that the corporate governance sub-provisions of shareholders, public disclosure/ transparency and stakeholders had positive impact on market performance, while board structure was irrelevant
Keywords: İktisat; İşletme